General Strain Theory and Collegiate Drinking Patterns Among African American Female Students - Walton, Isis N. (American journal of criminal justice, 2015)
Collegiate drinking, its prevalence and the associated problems it poses have been a national concern for over 30 years. Recent studies indicate that alcohol related issues are still a problem for college students. As research continues to describe the patterns of college students drinking patterns based on frequency and quantity, the literature does not specifically reflect the drinking patterns of African American college students. Further, research is also limited in examining the drinking patterns of college students attending Historically Black Colleges versus those attending majority serving institutions. This research focuses on the drinking patterns of African-American women ( N = 140) attending a Historically Black College/University (HBCU). Specifically, the General Strain Theory (GST) is used to analyze the indicators of African American women collegiate drinking habits. Our findings indicate that strain sparked depressive issues, which resulted in coping (i.e. binge drinking). Moreover, the more days of stressful life events increased the likelihood of depression which increased the likelihood of binge drinking.